A moral no racionalismo lockeano - Arndt, Eva Maria Gomes Soares (2021)
The main subject of this thesis is the Lockean approach on morals and ethics. Concerning these issues, John Locke stops working around the empiricist school of thought to focus on the rationalist one. Therefore, we have noticed that there is a dichotomy in the ideas of substances, relations and mixed modes, which defined our analytical journey. The hypothesis presented herein involves Locke showing how hedonism is justified by rationalism but not implying there is something innate therein. For Locke, morals concern a social phenomenon as it regards the ideas of happiness of social wellbeing each civilization considers pertaining for them; meanwhile, ethics concerns the judicative proposition from those moral rules. Our study will confirm this hypothesis primarily focusing on the sociological empiricism as the logic of beingtogether, which Locke details when addressing historical stages. However, this historical approach shall not be seen as the defense of a moral relativism as it would mean that Locke would no longer be defending the natural law, which he actually vehemently defends. As for reason, we take his pedagogical interpretation of said principle, which is to be developed by means of the formal education. Locke highlights the role of abstraction and considers this concept essential to develop the basis for the human action and the creation of laws. As for passions and moderation, we have noticed Locke thinks of the individual person not only as someone who must repeat a given behavior but as a being provided with reason and will that guide their choices. During our research, we have highlighted the Lockean defense for the ideas of relations and that in the ideas of mixed modes, morals concern knowledge as bound to reality, not as a mere probability. Locke’s approach in this case is different from the one concerning the ideas of substances, in which there is a clear distinction between real and nominal essences. However, concerning ethics, the archetype inhabits the idea that projects itself as its model, naming everything that there is. Therefore, this study leads us to consider how important language is. Basically, the Lockean approach makes us reflect on a constant fact of human condition — the need to develop models for the actions and project judicative judgments on them. Since this human condition remains noticeable on the current days, it deserves to be reflected upon.